Providing weight management via the workplace. Issue 3 (14th September 2015) - Barber, Jenny; Hillier, Sarah E; Middleton, Geoff; Keegan, Richard; Henderson, Hannah; Lavin, Jacquie
Abstract : Purpose: – The purpose of this paper is to assess the feasibility and benefits of providing weight management support via the workplace. Design/methodology/approach: – Quasi-experimental design using non-random assignment to a 12-week Slimming World (SW) weight management programme, either within the workplace or at a regular community group. Weight was recorded weekly and a 39-item questionnaire focused on mental and emotional health, self-esteem, dietary habits and physical activity habits administered at baseline, 12 weeks, six and 12 months. Findings: – In total, 243 participants enroled (workplace n =129, community n =114) with 138 completers (defined as those weighing-in at baseline and attending at least once within the last four weeks; workplace n =76, community n =62). Completers reported a mean weight change of −4.9 kg±3.4 or −5.7 per cent±3.8. Mental and emotional health scores increased ( p < 0.05) from baseline to 12 weeks. Self-worth scores increased ( p < 0.05) from baseline to 12 weeks, six and 12 months. Healthy dietary habit scores increased and unhealthy dietary habit scores decreased ( p < 0.05) from baseline to 12 weeks, six and 12 months. Healthy physical activity habit scores improved ( p < 0.05) from baseline to 12 weeks and six months. There were no significant differences between groups. Research limitations/implications: – Participant demographic was predominantly female (94 per cent) aged 42.3 years, with only 13 men participating. Practical implications: – The results support the use of a 12-week SW weight management programme as a credible option for employers wanting to support staff to achieve weight loss and improve psycho-social health outcomes which could lead to improvements in quality of life and work performance. Originality/value: – Provides evidence for the delivery of weight management support via the workplace.